2018
DOI: 10.1111/jfb.13756
|View full text |Cite
|
Sign up to set email alerts
|

Growth and otolith morphology vary with alternative reproductive tactics and contaminant exposure in the round goby Neogobius melanostomus

Abstract: Round goby Neogobius melanostomus sagittal (saccular) otolith morphology was compared between males of the two alternative reproductive tactics (termed guarder and sneaker males) and between males captured from sites of high or low contamination. Otolith size increased with fish size and also displayed an ontogenetic shift in shape, becoming relatively taller as otoliths grew in size. Despite a considerable overlap in age between males adopting the two reproductive tactics, size-at-age measurements revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 78 publications
(103 reference statements)
1
18
0
Order By: Relevance
“…Bose et al . (2018) confirmed that N. melanostomus otolith size increased with fish size and also displayed ontogenetic shifts in shape becoming more elliptical with an increase in the otolith size. They also noted differences in the otolith weights of sneaker and guarder males (the latter had lighter otoliths) and also subtle otolith shape differences between the two male reproductive tactic groups and between fish caught at sites where they were exposed to high and low contamination.…”
Section: Discussionmentioning
confidence: 63%
“…Bose et al . (2018) confirmed that N. melanostomus otolith size increased with fish size and also displayed ontogenetic shifts in shape becoming more elliptical with an increase in the otolith size. They also noted differences in the otolith weights of sneaker and guarder males (the latter had lighter otoliths) and also subtle otolith shape differences between the two male reproductive tactic groups and between fish caught at sites where they were exposed to high and low contamination.…”
Section: Discussionmentioning
confidence: 63%
“…This study provides evidence for the occurrence of alternative male mating strategies in round goby during their ongoing invasion of the upper Danube River (Table 2). Although this finding is novel in the context of a biological invasion process in the upper Danube River, alternative male mating strategies had been inferred for other round goby invasions, but with substantially different proportion estimates: whereas only about 4% round gobies were identified as sneakers in the invaded upper Danube River, much higher values of 40.6% in the River Rhine in the Netherlands (Bleeker et al 2017), and 39.3% (Bose et al 2018), 12 and 51% (Marentette et al 2009(Marentette et al , 2010 in the Great Lakes in the USA were found. A comparison of such proportions is challenging, however, because populations have different (invasion) histories, and exhibit different densities of conspecific and interspecific competitors (Cerwenka et al 2018), among other parameters.…”
Section: Discussionmentioning
confidence: 80%
“…Sneakers try to hide their male status by imitating females to fertilize foreign conspecific spawns (Taborsky et al 2008). Sneaker round gobies have a light mottled coloration, larger accessory sperm glands, a higher sperm volume, reduced 11-ketotestosterone levels (all: Marentette et al 2009), significantly larger testes, and heavier otoliths (both: Bose et al 2018). In the upper Danube River in Germany, round goby invasion processes, including spread, autecology, and impact on other species are well-studied (Brandner et al 2013a(Brandner et al , b, 2015Cerwenka et al 2014Cerwenka et al , 2017Cerwenka et al , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Age was estimated by examining otoliths cleared in glycerol (Kostûčenko 1961). Although sectioned and stained otoliths were recently recommended for age reading in the goby (Florin et al 2018), earlier studies were mainly conducted using whole otoliths (Kostûčenko 1961;Sokołowska and Fey 2011;Azour et al 2015;Bose et al 2018). Hence, we also applied whole sagittal otoliths to obtain comparable data with previous studies.…”
Section: Methodsmentioning
confidence: 99%